2012
DOI: 10.1590/s1020-49892012000400001
|View full text |Cite
|
Sign up to set email alerts
|

Modelo para estimación del comportamiento epidémico de la influenza A (H1N1) en México

Abstract: It was demonstrated that several epidemic scenarios occurred at the national level. It is suggested that heterogeneous patterns at the state level be taken into account in decision-making on the adoption of measures to mitigate influenza epidemics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…13 With similar methodology, was analyzed the influenza epidemic occurred in Mexico in 2009, and demonstrated values of R 0 from 1.2 to 1.6 in the first outbreak, and R 0 from 2.2 to 3.1 in the second outbreak, observing that in most states occurred epidemic. 14 In this study, it was observed that states which presented more than one outbreak, in general, the value of R 0 was very high in the first outbreak, and possibly representing a trend for new waves of epidemic.…”
Section: Discussionmentioning
confidence: 55%
“…13 With similar methodology, was analyzed the influenza epidemic occurred in Mexico in 2009, and demonstrated values of R 0 from 1.2 to 1.6 in the first outbreak, and R 0 from 2.2 to 3.1 in the second outbreak, observing that in most states occurred epidemic. 14 In this study, it was observed that states which presented more than one outbreak, in general, the value of R 0 was very high in the first outbreak, and possibly representing a trend for new waves of epidemic.…”
Section: Discussionmentioning
confidence: 55%
“…El modelo concierne las variaciones las tres poblaciones (susceptible, infectada y recuperada) a través de la tasa de infección y el período infeccioso promedio. 20,21…”
Section: I S C U S I ó Nunclassified
“…El modelo concierne las variaciones las tres poblaciones (susceptible, infectada y recuperada) a través de la tasa de infección y el período infeccioso promedio. 13,14 Consecuentemente, es vital identificar una población objetivo en la que las predicciones que convenzan una…”
Section: Señal De Rastreounclassified